2017
DOI: 10.1210/jc.2016-3827
|View full text |Cite
|
Sign up to set email alerts
|

Peak Bone Mass and Bone Microarchitecture in Adults Born With Low Birth Weight Preterm or at Term: A Cohort Study

Abstract: Both low-birth-weight groups displayed lower PBM and higher frequency of osteopenia/osteoporosis, implying increased future fracture risk. The most pronounced bone deficit was seen in VLBW adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 32 publications
8
46
1
3
Order By: Relevance
“…Lower bone accretion in preterm infants born SGA than in infants born AGA, independent of body size, suggest that prenatal conditions for bone accretion may not be replicated postnatally [84]. Lower body weight in infants born SGA was suggested as a potential risk factor for fracture [85] and an increased predisposition for fracture as a result of lower peak bone mass and higher risk of osteopenia was reported in young adults born SGA [86]. A study involving 15 preterm infants born SGA suggested that they may be at increased risk of low bone mass in adult life [87], with some data supporting that early life weight gain, especially peak weight velocity may be related to bone health, as assessed by vertebral cross sectional area, in adult life [88].…”
Section: Bone Strengthmentioning
confidence: 99%
“…Lower bone accretion in preterm infants born SGA than in infants born AGA, independent of body size, suggest that prenatal conditions for bone accretion may not be replicated postnatally [84]. Lower body weight in infants born SGA was suggested as a potential risk factor for fracture [85] and an increased predisposition for fracture as a result of lower peak bone mass and higher risk of osteopenia was reported in young adults born SGA [86]. A study involving 15 preterm infants born SGA suggested that they may be at increased risk of low bone mass in adult life [87], with some data supporting that early life weight gain, especially peak weight velocity may be related to bone health, as assessed by vertebral cross sectional area, in adult life [88].…”
Section: Bone Strengthmentioning
confidence: 99%
“…A recent body of research suggests that lower BW is associated with a variety of diseases of adulthood, including cardiovascular diseases, diabetes, hypertension, and other metabolic disorders (Godfrey & Barker, ). Additionally, low BW has been associated with potential risk for depression and anxiety in adulthood (Van Lieshout et al, ), increased fracture risk (Balasuriya et al, ), and neurodevelopmental difficulties including Attention Deficit Hyperactivity disorder (Momany, Kamradt, & Nikolas, ), among other health‐related conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Однако в настоящем исследовании, ожирение в подростковом возрасте по анамнестическим данным не встречалось, а дефицит массы тела выявлен только в 1 группе, у 11 пациенток. Была выявлена взаимосвязь между дефицитом массы тела в подростковом возрасте и МПК у родильниц, что вероятно связано с нарушением формирования пика костной массы [13].…”
Section: обсуждение основного результата исследованияunclassified